Isolation and characterization ofserum immunoglobulins of Cyprinus carpio - SOOD, NEERAJ; RATHORE, GAURAV; SWAMINATHAN, T RAJA; ABIDI, REHANA; MISHRA, B N; LAKRA, W S (The Indian Journal of Animal Sciences, 2011)
Common carp (Cyprinus carpio) immunoglobulin (Ig) was purified from serum by affinity chromatography using bovine serum albumin as capture ligand. The purified Ig had a molecular weight (MW) of820 kDa as determined by gel filtration chromatography. The MW of heavy and light chain of common carp Ig was 73.7 and 25.3 kDa, respectively, in SDS-PAGE. In no -reducing SDS..PAGE, 3 bands of different MW were observed, which were presumed to be of different forms of Ig. Â